From the History of Establishment of the “Dutorchilar” Ensemble after Named Ganijan Toshmatov (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the 40th anniversary of the creation of the ensemble "Dutorchilar," named after Ganijon Toshmatova (Ensemble) "Dutaristok." The author of the article is the participant of the first structure of the ensemble. The basic events and the facts are stated on the basis of its personal practice and memoirs. In the article is described, along with the consecration of the process of formation of an ensemble, separate worthy events in its creative way, and also separate sketches of organizing and tutorial qualities of the head of the company are made by G’anijon Toshmatov.